Socioeconomic Status and Obesity Relationship in Non-Menopause Women Aged 15-49 Years in Tehran, Iran - K Mohammad; B Golestan; R Majdzadeh; R Chaman; S Nedjat; M Karimloo; M Karimloo (Tehran University of Medical Sciences, 2009)
"nBackground: To investigate the association between socio-economic status and obesity in non-menopause women aged 15-49 years in Tehran, Iran."nMethods: This study was based on Iran National Health Survey conducted in 1999. Obesity is defined as a Body Mass Index over ≥30. Constructed area (per-person), educational level and job are considered as factors indicating the socioeconomic status. The results have been adjusted for age and mental health using univariate and multiple logistic regression.  "nResults: A total number of 2859 non-menopause women aged 15-49 yr from urban areas of Tehran have been studied. The prevalence of obesity and overweight were 16.4% and 28.4% respectively. Women aged 30-49 yr had greater risk of obesity (adjusted OR=2.53, 95%CI: 1.99-3.20). Comparing with students, homemakers and employees were at higher risk of obesity (adjusted OR= 4.33, 95%CI: 2.47-7.76, adjusted OR= 2.82, 95%CI: 1.41-5.63 respectively). Those with >= 12 yr of education had lower risk of obesity compared to illiterate women (adjusted OR=.57, 95%CI: 0.38-0.86)."nConclusion: The role of social factors is dominant over economic factor on obesity. This fact should be considered as one of the most important research priorities in future researches.